2000
DOI: 10.1063/1.480816
|View full text |Cite
|
Sign up to set email alerts
|

The vibrational structure of benzene adsorbed on Si(001)

Abstract: Articles you may be interested inVibrational characterization of ethylene adsorption and its thermal evolution on Si ( 001 ) -( 2 × 1 ) : Identification of majority and minority species J. Chem. Phys. 133, 054705 (2010); 10.1063/1.3469974 Vibrational and structural properties of OH adsorbed on Pt(111) Electronic and vibrational structure of thin films of bithiophene: Undoped and alkali-doped states J. Chem. Phys. 110, 8060 (1999); 10.1063/1.478707 Density functional investigation of the geometric and electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 17 publications
1
35
1
1
Order By: Relevance
“…6,9,13,15,28,31 A similar butterfly structure has been found also for benzene adsorption on Ge͑100͒ and on a Ge monolayer on Si͑100͒. 33 This dominant benzene phase is related to the main feature in the thermal desorption spectrum of the saturated benzene monolayer on Si͑100͒.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…6,9,13,15,28,31 A similar butterfly structure has been found also for benzene adsorption on Ge͑100͒ and on a Ge monolayer on Si͑100͒. 33 This dominant benzene phase is related to the main feature in the thermal desorption spectrum of the saturated benzene monolayer on Si͑100͒.…”
Section: Introductionmentioning
confidence: 81%
“…The lowest energy was found for the TiB structure by recent ab initio calculations. 10,12,14 On the other hand first-principles DFT cluster calculations by Birkenheuer et al 32 and Staufer et al 9 found excellent agreement between experimental and theoretical vibrational spectra only for the 1,4-cyclohexadienelike adsorption complex. Recent work using DFT with periodic boundary conditions was able to reproduce the HREEL spectra including the correct relative intensities.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations